Time to Build and the Business Cycle - Matthias Meier (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
Investment is central for business cycles and a key characteristic of investment is time to build (TTB). I document that TTB is volatile and largest during recessions. To study these fluctuations, I develop a model. In the model, the longer TTB, the less frequently firms invest, and the less investment reflects productivity, which worsens the allocation of capital. In the calibrated model, one month longer TTB lowers GDP by 0.5%. Empirical evidence corroborates the quantitative results.
Keywords: C32; C68; D92; E01; E22; E32; 330